GE_GERICHTE P/2000/2012 vom 6. Mai 2014 - GE Cour de justice (2014)
CLASSEMENT DE LA PROCÉDURE; FRAIS JUDICIAIRES; PRÉVENU; PROSTITUTION | CPP.319; CPP.426; CPP.431; CP.195; CP.199; Lprost.1; LRBDH.69